Distintion Principle dalam Hukum Humaniter sebagai Jaminan Penghormatan Terhadap Hak Asasi Manusia dan Perspektifnya Menurut Syari’at Islam - Palupi, Dwi Astuti; Rosra, Deswita (Nagari Law Review, 2023)
Human rights violations often occur when war / armed conflict disputes occur that cause damage and destruction, even involving people who are not involved in the war. Humanitarian law has firmly regulated the protection of victims who are not active in the war by applying the "Distinction Principle”. This "Distinction Principle" is also regulated in the Islamic legal system. Islamic law strictly distinguishes between combatants and non-combatants as far as the non-combatant population consists of women and the elderly who do not participate in war. Islamic law also prohibits killing children because they are among the weak and powerless to kill or participate in war. This writing aims to discuss the meaning of the Distinction Principle according to Humanitarian Law in the framework of respect for human rights and to understand the Distinction Principle in the Islamic Shari'a Perspective. In writing this article, normative legal methods, namely library research, were used on library materials to obtain secondary data, then the data was analyzed qualitatively. The study's results regarding the protection of human rights are closely related to the nature and limits of human rights, which are the basis for the protection of human rights. Islamic law has regulated the distinction principle in Humanitarian Law both in the Qoran and Hadist.